Diseño de un plan de control de incendios a partir de la determinación de la masa combustible en la Unidad Académica Caren. - Cevallos Polanco, Polivio Adolfo (2014)
This research develops the design of a fire control plan at Unit of Agricultural Sciences and Natural Resources CAREN at Technical University of Cotopaxi; which began with of observation the farm in the Academic Unit, location of existing resources, inventory and quantification to the development of diagnostic work. Riske were evaluate in a matrix, the mass of fuel throughout the unit was calculated, different methods to control fire hazards were analized after that we select Meseri. The results determined that the risks of fires ranging from low to medium without being able to rule out larger fires. In Chapter V as a proposed design fire control system, a preventive plan structured was developed and if it had accepted the short term. The hypothesis tested in this study is the absence of a fire control system shows the stocks of hazards and risks in the CAREN Unit. The proposed scheme provides all preventive measures to be developed to avoid such incidents.